The rehabilitation of the aparchai in imperial period - Gordillo Hervás, Rocío (ARYS. Antigüedad: Religiones y Sociedades, 2020)
This article addresses the restoration of the aparchai rituals which, despite having previously been the symbol of subjection of the east Greek and west Greek population under the Athenian polis, were restored under the rule of emperor Hadrian. The analysis of this restoration will allow for a new definition of such ritual elements as the unifiying factor for the new hellenic community which took form around the second century AD.